PRESCRIPTION AUDITING BASED ON THE WORLD HEALTH ORGANIZATION (WHO) PRESCRIBING INDICATORS IN OUTPATIENT DEPARTMENT OF A TEACHING HOSPITAL IN KERALA - T H, DHANYA; K B, SANALKUMAR; M A, ANDREWS (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study were to study the pattern of major drug groups prescribed, assess the Rational Prescription pattern by measuring the WHO Core Prescribing Indicators and to assess the quality of the prescriptions by assessing the legibility of prescription in the outpatient department of a tertiary care hospital. Methods: It was an analytical cross-sectional study done in hospital pharmacy for a period of 6 months. Approval from Institutional Research Committee and Institutional Ethics Committee was taken before starting the study. Sample size was taken as 1020. Results: One hundred and twenty prescriptions were analyzed. About 49% prescriptions were of males and 54% of females. Mean age of the patients were 46 years. A total of 3557 medicines were prescribed in 1020 prescriptions. Due to lack of legibility, we were unable to decode 122 medicines out of 3557 medicines prescribed. The dosage forms prescribed were; oral 87.4%, injections 1.4%, inhalational agents 0.4%, and topical agents 10.8%. Average number of medicines per prescription was 3.5. Percentage of medicines prescribed by generic name was 45%. Percentage of antibiotics per prescription was 24.8%. Percentage of injections per prescription was 4.8%. Percentage of medicines prescribed as per NATIONAL essential drugs list (EDL) was 3.2% and as per the WHO EDL was 2.6%. Percentage of fixed dose combinations (FDCs) was 6.5%. Conclusion: It was evident that polypharmacy was present as indicated by the average number of medicines prescribed. Medicines prescribed by generic name and from Essential Medicine List were less in number. Antibiotics and injections prescribed was in conformity with the WHO recommended values, which means that there was no irrational use of antibiotics and unwanted use of injectables. Percentage of FDCs was 6.5%. Most commonly prescribed drug was Ranitidine as per our study. Hence, as per this study, prescribers did not follow prescribing core indicators of the WHO closely, except for two indicators. The quality of prescriptions with respect to legibility and clarity was found to be optimal.